Simple Farming Business Bookkeeping in Nusa Serasan Village, Sungai Lilin District, Musi Banyuasin Regency - Abubakar, Rafeah; Iswarini, Harniatun; Pratami, Puri (Universitas Muhammadiyah Palembang, 2021)
The farming bookkeeping system is still a dilemma for women farmers in Indonesia because most of them do not have complete records of the income and expenses of their farming activities. As a result, farmers cannot determine the price set and the real profit obtained. This community service activity aims to increase the knowledge of farmers, especially female horticultural farmers, about farming bookkeeping and to improve the community's ability to make farming books. This activity was held in Nusa Serasan Jaya Village, Sungai Lilin District, Musi Banyuasin Regency on February 16, 2021. In this activity, the methods used were lectures and simulation practices. The presentation of the material using the lecture method and two-way discussion, followed by the simulation practice of doing simple farm bookkeeping. The results of the training activities show that the knowledge of female horticultural farmers in farming bookkeeping is still low. However, the success rate of participants in making simple farming bookkeeping is still low. Based on the results of these activities, it is recommended that participants receive retraining in filling out farm bookkeeping.